Outcome of 500 cases of transurethral resection of Prostate (TURP) in District level teaching Hospital (Bangladesh Journal of Medical Science, 2013)
Type of Study: This is a prospective study in a district level teaching from 1st march 2003 to December 2008. The sample size was n 500. All Patients were evaluated with history, clinical examination and allied investigations. As per selection criteria we did TURP and each patient was followed up to six months. Purpose & Importance of TURP: It has been established that open prostatectomy has got higher morbidity than that of transurethral resection of prostate (TURP). The shorter hospital stay, early institution to working place, minimum blood loss, and acceptable financial involvement makes it excellent patients compliance. Method: The prospective studies include n 500 cases of LUTS predominately obstructive voiding symptoms. After evaluation & fulfilling the selection criteria standard TURP were done in all cases. Result: The mean Q max improved in n 476 cases (from 6.68 ml/ sec. to 17.47ml/second) in early post-operative period. Among others most of the cases improved within 06 months. Some of the cases (0.25%) needs secondary procedure for late complications like stricture urethra. Erectile dysfunction was not a major problem in our series. Death noticed in two cases in post operative ward due to cardiogenic shock. Conclusion: The outcome of the present study has been compared with other studies and it appears that TURP is an excellent minimally invasive procedure for the management of symptomatic BPH. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 186-191 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14948